IMPLEMENTASI PROGRAM EKSTRAKURIKULER DALAM PEMBELAJARAN QOWAID BAHASA ARAB SISWA MA MUHAMMADIYAH KOTA BIMA - Nuraini, Nuraini; Nurlaili, Nurlaili; Wahyuningsih, Sri (Raudhah - Proud To Be Professional, 2025)
Based on the results of preliminary observations made by researchers at MA Muhammadiyah Bima City that students when following Arabic language learning they have difficulty in understanding qowaid or Arabic grammar. One of the reasons is because of inappropriate learning techniques, methods that are too monotonous (lecture method), too monotonous on KEMENAG books and the lack of learning hours at school. So this research aims to find out the Implementation of Extracurricular Programs in Learning Arabic Qowaid Students Ma Muhammadiyah Kota Bima. This research will be conducted at MA Muhammadiyah Bima City, West Nusa Tenggara. This research uses Qualitative Research with a Case Study Approach. Data Collection Techniques are Observation, Interview and Documentation. Data Analysis Techniques are Data Reduction, Data Presentation and Conclusion Drawing. Based on the results of this study, the extracurricular program in learning Arabic qawāʿid at MA Muhammadiyah Bima City can be used as an effective and applicable language education development model. The integration between academic learning and extracurricular activities is a real solution to the classic problems in teaching Arabic grammar. With a more creative, communicative, and experience-based approach, students are not only invited to understand the theory, but also able to use it in real life.